Using social sensing to evaluate the effect of spatial planning: A case study of Yangtze River Delta Urban Agglomeration in China - Zhichao He; Wei Zhai; Chunhong Zhao (Frontiers of Architectural Research)
The increasing impacts of human activities on sustainable development have promoted the use of spatial planning as an essential policy tool to governing human activities patterns. However, the effect of spatial planning on such patterns remains insufficiently unexplored. In this study, we used Point of Interest (POI) data and spatial statistical methods to analyze the spatial patterns of human activities in the Yangtze River Delta (YRD) Urban Agglomeration in China between 2018 and 2022, and then evaluated the conformance between these patterns with the planned spatial patterns outlined in the YRD Urban Agglomeration Development Plan. The results show that while the development plan is effective on promoting spatial integration of human activities, it has not fully achieved the intended patterns. Shanghai's prominence as a business center has strengthened over time, though its population and industrial centers have eroded. The Su-Xi-Chang metropolitan area illustrated a high level of spatial integration and has emerged as a key industrial function zone. However, many peripheral cities, including those in Anhui Province, northern Jiangsu Province, and southern Zhejiang Province, remain poorly integrated into the YRD Urban Agglomeration. To conclude, we recommend wider application of social sensing data on plan evaluation and highlight a diverse set of collaborative strategies to strengthen spatial integration between central and neighboring cities, as well as between metropolitan areas within the agglomeration.